Understanding the coupling between MIM cavities due to single and double Tamm plasmon polaritons - Missoni, Leandro Luis (2023)
The interplay between light and matter plays a crucial role in various applications, ranging from sensor technologies to integrated optoelectronic architectures. In this contribution, a systematic numerical study is made over the symmetry role of the 1D photonic structures (PhSs) containing a low number of slabs embedded in thin metal layers, in order to find the adequate conditions to enhance the quality factor of resonances and energy confinement in the subwavelength scale. We show the existence of single and double Tamm plasmon polaritons (TPPs) states according to the symmetry of the PhS, which allow to tune weak and strong coupling regimes with Metal–Insulator–Metal (MIM) platforms combined in a unique MIM-PhS-MIM structure. We found that while weak coupling is observable between MIM and PhS states at the PhS cavity mode wavelengths, strong coupling among the 2 MIMs and the PhS is obtained only at the TPP resonance wavelengths, exhibited by anti-crossing splittings at adequate insulator thicknesses. We found that for the double Tamm plasmon polaritons, the energy splitting can reach up to 134 meV, unlike the single TPPs where the maximum energy splitting is on the order of 50 meV. The degree of coupling was explained by the implementation of a variational method that exploits the analogy the optical superlattice herein proposed and an analogous superlattice quantum well. This article shows that TPP resonances are responsible for the coherent coupling between the two MIMs placed at a long distance given by the PhSs. Thus, these platforms provide an interesting and experimentally accessible route for the coupling of emitters in optoelectronic devices.